Targeting mitochondrial ClpP: structural insights and therapeutic potential of ClpP agonists in cancer therapy - Mowei Kong; Yang Yu; Shuai Shao; Chunxiang Zhang (Oncology Reviews)
Mitochondrial “powerhouses” play a central function in cellular metabolism and energy generation. Their dysregulation is directly correlated with a myriad of diseases, among them cancer. The serine protease ClpP, accompanied by its cochaperone ClpX, is a principal homeostatic regulator in mitochondrial function by degrading aberrant proteins in order to preserve mitochondrial integrity. Recently, evidence suggests ClpP is overexpressed in many cancer cells and, as such, is an appealing target for drug therapy. In this review, current information about the structure, physiological function, and therapeutic promise of mitochondrial ClpP in oncology is summarized. We provide an overview about the mechanistic rationale behind ClpP agonists as novel anticancer drugs, their regulation in cell signal transduction, and the major challenge in the creation of small molecules that specifically activate human ClpP, but not bacterial ClpP. The review highlights the therapeutic promise of ClpP agonists as a novel approach in cancer therapy, presenting their prospective potential for cancer treatment by focusing on an unexplored mitochondrial target.